Consequences of Obesity Associated Factors Caused Coronary Heart Disease. A Comparative Clinical Study - Abubakar Tariq, Jazib Andleeb, Awais Anwar, Amna Akram, Rizwana Hussain, Naveed Shuja, (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: The main objective of this study was to check clinically that Coronary Heart Disease in our local population caused by obesity. Study design: It is a comparative clinical study. Place and duration: Current clinical study was conducted in Lahore Medical & Dental College Lahore, Pakistan from December 2021to March 2022. Methodology: In Group X, 25 normal individuals were selected while in Group Y, 75 patients with Coronary Heart Disease were considered respectively. Intensity of Shoulder or arm pain, Shortness of breath, lipid profile, BMI, oxygen saturation, systolic and diastolic blood pressure and electrocardiogram (ECG). Lipid profile were performed through blood sample, Oxygen saturation levels were measured through oximeter, blood pressure with sphygmomanometer. The bio-statistically model SPSS was applied for the presentation of collected raw data. Results: Different parameters such as BMI, systolic and diastolic blood pressure, Intensity of Shoulder or arm pain, oxygen saturation, blood serum cholesterol, blood serum triglycerides, blood serum LDL, blood serum HDL levels and electrocardiogram (ECG) were measured comparatively in current study. The levels of these variables in Group-X and Group-Y were (18.02±01.02, 118.1±01.01, 72.01±0.01, 0.01±0.01, 99.0±0.03, 198.01±0.04, 138.02±0.02, 125.01±0.03, 45.01±0.01), (28.01±01.04, 178.0±01.03, 96.01±09.04, 90.01±0.02, 94.0±0.03, 268.01±0.01, 208.01±0.04, 185.01±0.01, 35.01±0.04) measured respectively. Conclusion: In present study different parameters such as BMI, systolic and diastolic blood pressure, Intensity of Shoulder or arm pain, oxygen saturation, blood serum cholesterol, blood serum triglycerides, blood serum LDL, blood serum HDL levels and electrocardiogram (ECG) were measured in both Group-X and Group-Y and a significant (P≤0.05) changes were observed in individuals of Group-Y than the Group-X comparatively. Keywords: Body mass index, Obesity, Coronary Artery Disease, Systolic and Diastolic Blood Pressure